Answer:
Airplane #1 equation: y=5/13x+42/13
Airplane #2 equation: y=1/3x+14
Step-by-step explanation:
So to find the slope of each airplane, you use the formula y2-y1/x2-x1. That means, for airplane#1 the equation will be 9-4/15-2. Simplify this and get 5/13. Then, for airplane#2, the equation will be 12-9/6-15. Simplify this and get 3/-9 and divide each side by 3 to get 1/-3 or -1/3. Next, use point slope formula to find the system of linear equations. Point slope formula is y-y1=m(x-x1). M is the slope. Use any point from the line. In this case, I will use (2,4). Tat means the first airplane's equation would be y-4=5/13(x-2). Then y-4=5/13x-10/13. Then, convert four into a fraction with a denominator of 13. This means, you have to multiply 4 by 13 to get 52/13. Add 52/13 to -10/13 to get 42/13. That means the first equation will be y=5/13x+42/13. The second equation point will be (6,12). This means the equation will be y-12=-1/3(x-6). Simplify this to get y-12=-1/3x+2. Simplify this to get y=1/3x+14. Therefore, Airplane#1 equation will be y=5/13x+42/13 and airplane #2 equation will be y=1/3x+14.
Hope this helps
Answer:
you have to show the way you did it like this
Step-by-step explanation:
79 ÷ 10 = 7r9
<span>2x + 4y = 36
3x - 4y = -6
--------------add
5x = 30
x = 6
</span>2x+4y=36
2(6)+4y=36
12 + 4y = 36
4y = 24
y = 6
answer
<span>(6, 6) is a solution of equations
</span><span>(4,7) is NOT a solution of equations</span>
We have that
f(x) = –4x²<span> + 24x + 13
</span>
we know that
The vertex form for a parabola that opens up or down is:
f(x) = a(x - h)^2 + k
in the given equation, <span>a=-4</span><span>, therefore we add zero to the original equation in the form of </span><span>4h</span>²<span>−4h</span>²
f(x) = –4x² + 24x + 4h²−4h² +13
<span>Factor 4 out of the first 3 terms and group them
</span>f(x) = –4*(x² -6x +h²) +4h² +13
<span>We can find the value of h by setting the middle term equal to -2hx
</span>−2hx=−6x
<span>h=3</span><span> and </span><span>4h</span>²<span>=<span>36
</span></span>f(x) = –4*(x² -6x +9) +36 +13
we know that the term (x² -6x +9) is equals to------> (x-3)²
so
f(x) = –4*(x-3)² +49
the answer isf(x) = –4*(x-3)² +49
Answer:
Yes, you can find the cube root of a negative number. The answer will be negative!
Step-by-step explanation:
Example: Find the cube root of -27
We know that a cube root is a number multiplied by itself 3 times (NOT MEANING THE NUMBER TIMES 3)
For example, The cube root of 27 positive is 3 because 3 x 3 x 3 = 27
But if we are using a negative number: It is really different because we got to know the rules.
The setup: -3 x -3 x -3 = -27
If we started with -3 x -3 first we know that a negative times a negative equals positive so the answer will be 9 positive, then we have this equation left:
9 x -3 = -27
The rule with this is a number times a negative is negative, so the answer of the question "Find the cube root of -27 is -3"